3D Printed PCB Microfluidics - Stefan Gassmann; Sathurja Jegatheeswaran; Till Schleifer; Hesam Arbabi; Helmut Schütte (Micromachines, 2022)
The combination of printed circuit boards (PCB) and microfluidics has many advantages. The combination of electrodes, sensors and electronics is needed for almost all microfluidic systems. Using PCBs as a substrate, this integration is intrinsic. Additive manufacturing has become a widely used technique in industry, research and by hobbyists. One very promising rapid prototype technique is vat polymerization with an LCD as mask, also known as masked stereolithography (mSLA). These printers are available with resolutions down to 35 µm, and they are affordable. In this paper, a technology is described which creates microfluidics on a PCB substrate using an mSLA printer. All steps of the production process can be carried out with commercially available printers and resins: this includes the structuring of the copper layer of the PCB and the buildup of the channel layer on top of the PCB. Copper trace dimensions down to 100 µm and channel dimensions of 800 µm are feasible. The described technology is a low-cost solution for combining PCBs and microfluidics.